The vault eaudiobook - Lovesey, Peter (Peter Diamond Mystery, 2017)
A skeletal hand is unearthed in the vault under the Pump Room in Bath, England, near the site where Mary Shelley wrote Frankenstein . Then a skull is excavated. The bones came from different corpses, and one is modern. Detective Superintendent Peter Diamond must solve a series of crimes including murder and forgery, requiring a knowledge of history, nineteenth-century art, literature . . . and human nature.